Thrombotic Microangiopathy Complicating Cyclosporine in Renal Transplant Patients - Safa Al-Mukhtar (Advanced Medical Journal)
Background and objectives: Experience with cyclosporine associated thrombotic microangiopathy in renal allograft recipients is generally anecdotal; detailed descriptions of clinical behavior, therapeutic options and experience are also anecdotal and few. The aim of this study was to identify possible contributing factors to cyclosporine associated thrombotic microangiopathy, and to investigate therapeutic modifications that result in better graft survival in these patients.